Kajian Keterampilan Berpikir Kritis, Keterampilan Proses Sains dan Literasi Digital: Ditinjau Berdasarkan Gender - Dwi Agus Kurniawan; Darmaji Darmaji; Astalini Astalini; Sri Muslimatul Husna (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to analyze and find out the effect of critical thinking skills and science skills on digital literacy of class VIII F and VIII G students of SMPN 7 Muaro Jambi in terms of gender. The research method used is a mixed method with an explanatory design. The sampling technique in this study was purposive sampling with a sample of 56 students. The instruments used were critical thinking skills essay tests, KPS observation sheets, digital literacy questionnaires, and interview sheets. The quantitative data analysis technique used is descriptive statistical analysis and inferential statistics, while the qualitative data analysis technique used is the Miles and Huberman technique. The results of multiple linear regression tests show that there is an influence of critical thinking skills and science process skills on digital literacy. From the interview results it is known that critical thinking skills, science process skills, and digital literacy are classified as good. So, it can be concluded that there is a significant influence between critical thinking skills and science process skills on students' digital literacy.